Soft M-Separation Axioms in Dual Soft Topological Space - Maryam Sabbeh Al-Rubaie; Maryam Adnan Al-Ethary; Waleed Khalid Kadhim (Scientific Trends, 2023)
In this paper, some new weak separation axioms associated with the “soft dual local function” were obtained. As well as studying some of its properties and the relationship between it and the relationship between it and the other weak separation axioms
Keywords: second type of soft local function, m^(*∘)-space , m^(**∘)-space , m^(***∘)-space , m^(****∘)-space.